Anthropogenic Litter on Beaches With Different Levels of Development and Use: A Snapshot of a Coast in Pernambuco (Brazil) - Araújo, Maria C. B.; Silva-Cavalcanti, Jacqueline S.; Costa, Monica F. (Frontiers in Marine Science, 2018)
This research aimed to evaluate anthropogenic litter found on beaches with different levels of development and use along the coast of Pernambuco (northeast Brazil) to determine patterns in composition and origin. The study was conducted in January 2013 at nine beaches classified into three groups according to the level of urbanisation. At each beach, three sections measuring 100m long and 1m wide were defined along the high-tide waterline where all items of anthropogenic litter larger than 2 cm were visually counted and classified. The sections were separated by intervals of 100 m. Within each 100 m section, random stretches of 10 m were selected where all the visible plastic fragments with sizes between 0.5 and 2 cm were collected and bagged for subsequent counting. Sources of anthropogenic litter were divided into three categories, namely beach users, land-based (houses/residences), mixed, and fisheries. A total of 12,815 items were found on the nine beaches within the three transects on each beach (one survey per beach), with densities (items/m2) of 2.3, 5.7, and 6.3 for groups 1, 2, and 3, respectively. The most-represented items of anthropogenic litter in the evaluated samples were plastic, food scraps, and wood (wooden skewers). With respect to items composed of plastic, the majority were cigarette butts (45%). Additionally, cigarette butts made up 26% of all anthropogenic litter samples collected. A larger amount of fragments smaller than 2 cm occurred in all beaches; for this size fraction, the densities were 0.6, 0.5, and 0.76 items/m2 for groups 1, 2, and 3, respectively, which were 1.5, 2.5, and 1.65 times higher, respectively, compared to those of fragments larger than 2cm..The beaches with lower levels of urbanisation also had smaller quantities of anthropogenic litter. Items related to beach users were predominant for most of the beaches. The confirmation that beach users are primarily responsible for the generation of anthropogenic litter may contribute to the development of strategies to reduce the problem, such as installing bins and distribution containers for anthropogenic litter collection and designing educational campaigns for beach users.